Linguoconflictology of the Media Space: Study of Foreign Experience - Zhanzhigitov, S.Zh.; Bakytzhanova, A.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
This article aims to explore the foreign experience in linguistic conflictology within the media space through a comprehensive analysis of 910 publications indexed in the Scopus database from 1968 to 2024. The study employs content analysis, bibliometric techniques, and statistical data processing with SPSS to identify the main trends and directions in media conflict research. The findings indicate a growing academic interest in this topic, especially after 2000, with the United States, the United Kingdom, and Germany leading in publication activity. These results underscore the importance of media discourse in shaping public perception and influencing socio-political processes. Moreover, the study reveals that media conflicts often involve cultural, linguistic, and technological dimensions that require coordinated management strategies. By synthesizing global perspectives, the research provides practical recommendations for policymakers, media professionals, and academics seeking to mitigate conflicts in digital and traditional media environments and fosters more harmonious media interactions.
Медиакеңістік лингвоконфликтологиясы: шетелдік тәжірибені зерттеу
Лингвоконфликтология медиапространства: исследование зарубежного опыта
Keywords: media space; conflict; text; linguistic conflictology; linguistic analysis